Transformative Tourism: Catalyst for Economic Recovery and Poverty Alleviation Post-COVID-19 Pandemic - Muhammad Rahmad; Myrza Rahmanita (Green Publisher Indonesia, 2025)
The COVID-19 pandemic has caused an unprecedented global economic shock, causing a recession, increasing unemployment, and worsening poverty. In this context, tourism is emerging as a critical sector with the potential to overcome these challenges and drive economic recovery. This research explores the concept of Transformative Tourism as an innovative approach to overcoming the negative impacts of the recession, creating jobs, and alleviating poverty in the post-pandemic era. Through a comprehensive analysis of global case studies, this research reveals critical strategies for revitalizing the tourism sector sustainably and inclusively. Key findings highlight the importance of tourism product diversification, workforce skills development, use of digital technology, and collaboration between stakeholders. This research also emphasizes the central role of tourism in empowering local communities, especially vulnerable groups, through employment opportunities and small business development. By adopting a transformative approach, the tourism sector can catalyze equitable economic growth, poverty reduction, and social resilience in the face of post-COVID uncertainty. Policy implications of this research include the need for coordinated government support, investment in tourism infrastructure, and promotion of responsible tourism. This research provides valuable insights for policymakers, industry players, and academics seeking to harness the transformative potential of tourism to address pressing economic and social challenges in the post-pandemic era.